Presence of Tourism-Led-Growth Hypothesis in Pakistan: Empirical Evidence with ARDL Model - Hijazi , Muhammad Masood; Qamri , Ghulam Muhammad; Sidique , Abu Bakar; Khan , Qasim Raza; Akbar , Aqsa (Pakistan Journal of Humanities and Social Sciences, 2024)
Tourism has become the world’s third-largest export earning industry. According to the World Bank, in recent times international tourism has attracted a great attention and 7% of world’s total trade involves tourism. Tourism is considered one of the endogenous factors to boost the economic growth and development of any nation. It has versatile impacts on country growth and contributes directly and indirectly to GDP. The paper aims to bring forth confirmation of the tourism-led-growth hypothesis (TLGH) for Pakistan using time series data from 1995-2020 by incorporating inflation, international tourism, and tourism expenditure as regressors. For checking the stationarity of time series data, unit root tests Augmented Dickey-Fuller test (ADF) and Phillip Perron test indicate that Economic Growth and inflation are stationary at their first difference while tourism expenditure and number of international arrivals are stationary at level. ARDL approach has been utilized to establish the link to how tourism affects the economic growth of Pakistan and the Cumulative Sum of Recursive Residual (CUSUM) and CUSUM of square has been used to check the stability of the model. The result depicts that a long-run relation exists among the variables. Inflation has a negative and significant impact on economic growth while international arrival and tourism expenditure have a positive and significant impact on economic growth. Furthermore, to enhance tourism activities and attract foreign tourists, the government must focus on macroeconomic stability because such factors have a direct effect on tourism and thus multifaceted impact on economic growth.